Wireless multimedia communication systems: design, analysis, and implementation - Rao, K R. (CRC Press, 2014)
"PREFACE Wireless multimedia communication systems (WMCSs) have become one of the most important medium for information exchange and the core communication environment for business relations as well as for social interactions. This is a rapidly evolving field with growing applications in science and engineering. Millions of people all over the world use the WMCSs for a plethora of daily activities. As we move further to the information age, the rapid advancement will continue in all aspects of WMCSs technologies. Wireless technologies impact research fields in several disciplines. At the same time, wireless research has also benefited from ideas developed in other fields. How to effectively utilize the interdisciplinary research ideas to develop more efficient wireless technologies opens a new thread of research and design. After many years of research activities related to the optimization of the physical layer of radio networks, the focus is shifting in part towards system and applications level engineering and optimization, for an improved performance of wireless multimedia communications. New topics are introduced, most of them not only to incrementally improving current systems, but also to provide superior capacity, spectral efficiency and flexible operation to the next generation wireless systems (NGWSs). This can be achieved by extending the system bandwidth and pushing up the transmission rate by coordinating radio resources across adjacent cells for reduced interference in dense reuse of cellular networks, by introducing mesh networking components and smart antenna technology for spatial multiplex based transmission. "--